PERAN MEDIA SOSIAL DALAM PEMBENTUKAN AKHLAK SISWA DI MADRASAH TSANAWIYAH NEGERI BARITO SELATAN - Sari, Kartika Diah; Sangaji, Fahmi Arif (Al-Manba, 2025)
The main problems examined in this study include: what types of social media are used by students, what types of smartphones are used by students, and the role of social media in the formation of students' morals at the South Barito State Islamic Junior High School. The purpose of this study was to determine what types of social media are used by students, and how social media plays a role in the formation of students' morals at the South Barito State Islamic Junior High School. This study uses a descriptive qualitative approach, where the data is analyzed using data collection techniques through interviews and documentation. The subjects in this study were students of the South Barito State Islamic Junior High School, totaling 4 students in grade VII, 4 students in grade VIII, and 4 students in grade IX. The object of this study was the role of social media in the formation of students' morals at the South Barito State Islamic Junior High School. The data collected in this study were primary data and supporting data. The data sources of this study were respondents consisting of students and informants consisting of teachers and administrative staff. The results of this study indicate that Instagram is the most popular social media platform among students, and Android smartphones are the preferred smartphone, while iPhone usage is very limited among students. The role of social media among students varies, ranging from 1-9 hours per day, and positive interest in Islamic preaching content or lectures from certain religious teachers or preachers is also found. In addition, students also have their own favorite religious teachers or preachers. In this case, religious content on social media shows a specific consumption pattern among madrasah students, with a primary focus on lectures and Islamic preaching.